Pattern Drafting and Free-Hand Cutting Technique on Apparel Fit - Bakker-Edoh, Dymphna; Oigo, Dr. Bosibori; Mburugu, Prof. Keren G. (Journal of Marketing Studies, 2018)
Purpose: To assess the effect of pattern drafting and free-hand cutting technique on apparel fit. Methodology: The study employed a cross-sectional descriptive survey was considered adequate for this study as it has the advantage of soliciting respondent's views on the nature of the situation as it existed at the time of a study (Creswell, 2012; Mugenda, 2008). The design is an efficient way of collecting information of a large group of people within a short time using questionnaires. The survey design was deemed appropriate for this study as it has the advantage of seeking the views of informal dressmakers and tailors on the use of pattern drafting and free-hand cutting in apparel construction. It allowed for the use of both quantitative and qualitative techniques in the study. This paved way for better understanding of a phenomenon under study. The use of these methods offered the opportunity to have in-depth information and also the weakness in one method is compensated for by the strength in another method (Creswell, 2012). Results: Pattern drafting scored higher than free-hand cutting. Concerning how measurements were being taken, it was realized that there was great disparity between the two groups in the way measurements were taken and recorded. The group using pattern drafting scored good (75%), while the group using free-hand cutting had a low score of 34%. In other words, they showed very poor skills in taking measurement in all the apparel sewed. The implication is that measurement taking was a great problem that needed to be addressed as far as the use of free-hand cutting method is concerned. Proper taking and recording of measurement for future references was not part of their style. Standing position of clients during measurement taking was not given the proper concern. Unique Contribution to theory, practice and policy: The study recommended more vocational training on pattern drafting to increase the accuracy in dress crafting. Additionally, the study advocated for IDTA to enact policy to incorporate pattern drafting and other methods of apparel construction into the training curriculum of apprentices to develop interest in the use of these methods right from the onset.